Ligand design of a novel metal-organic framework for selective capturing of Pb(II) from wastewater. (1st February 2023) - Liu, Xiang; Tang, Jiali; Fu, Likang; Wang, Hao; Wang, Shuai; Xiong, Chao; Wang, Shixing; Zhang, Libo
Abstract: With the increasing pollution of lead in industrial wastewater, many researchers have tried to remove lead ions by various methods. However, while removing lead, some valuable metals are often removed, resulting in loss of economic benefits. It is necessary to develop new materials that can efficiently and selectively remove lead ions without affecting other metals. In this work, a novel Zr-based metal-organic framework adsorbent (UiO-DCCA) is synthesized for the efficient and selective capture of Pb(II) by a novel N, N'-(4carboxylic-pyridine-2, 6-diyl) dipicolinimidamide ligand. The selective adsorption experiment shows unique affinity of UiO-DCCA for Pb(II), and the maximum adsorption capacity is 353.29 mg/g. The adsorption mode is single-layer chemical adsorption that conforms with the pseudo-second-order kinetic and Langmuir isotherm models. Density functional theory calculations indicate that the electrostatic interaction of –NH and the chelation of CN assume a significant part in the adsorption process. This study shows the value of new self-designed organic ligands in metal-organic framework materials that selectively capture heavy metal ions. Graphical abstract: Image 1 Highlights: A self-designed zirconium-based MOF is synthesized by novel organic ligand. The adsorption capacity and distribution coefficient of UiO-DCCA on Pb(II) are 353.29 mg/g and 10.34. The capture mechanism is revealed by Mulliken charge distribution theory and frontier molecular orbitals. The binding energy and dipole moment of the optimal adsorption model for UiO-DCCA on Pb(II) are −0.626 eV and 14.722 D.